Application of STEAM method in learning in madrasah to improve student understanding - Kurniawati, Vira; Siswanto, Siswanto (Jurnal Inovasi Teknologi Pendidikan, 2024)
Islamic education in madrasah is important to form a generation of competent Muslims in the era of technology and science. The STEAM method integrates science, technology, engineering, art, and math in holistic learning. This study analyzes the application of the STEAM method in madrasah, focusing on Islamic education. The approach to this study uses qualitative descriptive analysis with data collection through observation, interviews, and document analysis. The madrasah teacher and 30 students who used the STEAM method were sampled. The results showed a positive impact on students' understanding of Islamic education. The integration of STEAM science enables the development of critical thinking, creativity, collaboration, and problem-solving skills. Students' interest and adaptability also increase. Madrasah teachers need to understand the STEAM method to integrate it into Islamic learning. The STEAM method prepares a holistic generation of Muslims for the future.